The Importance of Modern Tools and Methods in Agronomy - Gulaqa Anwari; Abdul Qadir Nabizada (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
With the rapid advancement of information and communication technologies, new opportunities have emerged to improve agricultural management. Precision agriculture, or site-specific crop management, is a farm management concept based on observing and responding to within-field variability. This concept is increasingly applied in irrigation and fertilization management through the use of proximal sensors that assess crop canopy characteristics in visible and thermal bands, as well as automated guidance systems based on the Global Positioning System (GPS). Remote sensing refers to acquiring information about an object without physical contact, using satellites, aircraft, or ground-based equipment. Other tools include simulation models and computer programs based on equations that describe crop responses to management practices (such as planting density) and environmental factors (climate and soil). These data can be integrated with remote sensing information to enable large-scale analysis, prediction, and improved site-specific farm management.